An Evolutionary Perspective on Adult Female Germline Stem Cell Function from Flies to Humans - Woods, Dori C.; Tilly, Jonathan L. (Seminars in Reproductive Medicine, 2013)
The concept that oogenesis continues into reproductive life has been well established in nonmammalian species. Recent studies of mice and women indicate that oocyte formation is also not, as traditionally believed, restricted to the fetal or perinatal periods. Analogous to de novo oocyte formation in flies and fish, newly formed oocytes in adult mammalian ovaries arise from germline stem cells (GSCs) or, more specifically, oogonial stem cells (OSCs). Studies of mice have confirmed that isolated OSCs, once delivered back into adult ovaries, are capable of generating fully functional eggs that fertilize to produce healthy embryos and offspring. Parallel studies of OSCs recently purified from ovaries of reproductive-age women indicate that these cells closely resemble their mouse ovary–derived counterparts, although the fertilization competency of oocytes generated by human OSCs awaits clarification. Despite the ability of OSCs to produce new oocytes during adulthood, oogenesis will still ultimately cease with age, contributing to ovarian failure. The causal mechanisms behind these events in mammals are unknown, but studies of flies have revealed that GSC niche dysfunction plays a critical role in age-related oogenic failure. Such insights derived from evaluation of nonmammalian species, in which postnatal oogenesis has been studied in depth, may aid in development of new strategies to alleviate ovarian failure and infertility in mammals.
Keywords: germline stem cell; oogonial stem cell; oogenesis; oocyte; ovary; human